Template-Mediated Formation of Colloidal Two-Dimensional Tin Telluride Nanosheets and the Role of the Ligands - Christian Klinke (The Journal of Physical Chemistry C, 2022)
We report the colloidal synthesis of 2D SnTe nanosheets through precursor hot-injection in a nonpolar solvent. During the reaction, an important intermediate – Sn-template – is formed which defines the confined growth of SnTe. This "flake-like" structure gives the first evidence for the possible 2D morphology formation prior to the anion precursor injection (TOP-Te). Additionally, we explore the role of each ligand in the reaction process. Thus, we explain the formation and morphology evolution of 2D SnTe nanostructures from a mechanism perspective as well as the role of each ligand on the molecular scale. The interplay of ligands provides the necessary conditions for the realization of stable low-dimensional SnTe nanomaterials with tunable size and shape.